Impacts of Coffee Agroforestry and Sustainability Certification on Farmers' Livelihood in Sumatra-Indonesia - Hanung Ismono; Bustanul Arifin; Katsuya Tanaka; Ryohei Kada (The Indonesian Forestry Certification Cooperation, 2022)
This study examines the impacts of coffee agroforestry system and sustainability certification on farmers’ livelihood in Sumatra-Indonesia. The study applies farm-income analysis and quasi-experimental impact evaluations by interviewing 408 coffee farm-households in Lampung Province. Propensity score matching (PSM) adopted here compares some matching characteristics of adopters of coffee agroforestry system and sustainability certification and the control groups. The results show that both coffee agroforestry systems and sustainability certification have positive significant impacts in improving economic benefits and environmental benefits, although the magnitudes slightly differ. Future policy shall provide better alternatives for farmers’ land-use systems that could ensure a better livelihood.